The Impact of Practicing Exercise and Risk Factors Categorize in Osteoporotic Concerning Postmenopausal Women (Analytical study using binary logistic regression) - Farooq Khaleel , Raed; Abduljabbar Ali , Abdulkaliq; Mohammed Hassoon , Suhair (Diyala Journal of Medicine, 2023)
Background: Osteoporosis is an illness that may be categorized as a "silent pandemic" because of its worldwide incidence. The essential characteristics of osteoporosis are bone mass reduction and degeneration in bone tissue's micro-architecture. Postmenopausal osteoporosis (PMO) seems to be the most prevalent skeletal disorder. Objective: To study investigates the influence of practicing exercise and physical activity as the most critical contributing factors of osteoporosis in postmenopausal women. Patients and Methods: A cross-sectional survey was conducted at Baghdad Teaching Hospital from July 1, 2021, to December 31, 2021. Data were collected directly through interviews using a special questionnaire. One hundred and fifty postmenopausal women with osteoporosis participated in this study. A rheumatologist clinically diagnosed all participants using a bone density screening (DEXA). Results: the current study's results indicate the prevalence of osteoporosis among postmenopausal women, with a higher percentage of 69.3% in the age group (≥50 years). 60.7% of all participants were overweight and obese according to body mass index (BMI). Calcium deficiency was found in 87.3% of the subjects, more than two third (76%) of them were not practicing exercises, and 86.7% suffered from vitamin D deficiency. Reclassifying the actual and wrong percentile demonstrates the accurate percentile (overall percentage = 78.7), 32 individuals were wrongly classified, and the probability of total error was reported at around 21.3%. The most important finding was that postmenopausal women with osteoporosis who exercised and participated in physical activity regularly were 13.7 times in better health than those who did not exercise. Conclusion: Exercising and physical activity lower risk factors for postmenopausal women. It is becoming more necessary to reconsider the importance of performing exercises in maintaining and enhancing postmenopausal women's health.